Predictors and health impacts of Ramadan intermittent fasting among patients with sickle cell disease - Alsalman, Mortadah Hadi; Alsalman, Zaenb; Alshams, Maryam Mohammed; Aljasem, Jinan Mohammed; Alsindi, Zahra Saleh; Almutairi, Amani Abdullah; Alsunaikh, Khadija Abdulrahman; Buali, Hadeel Hesham; Algadeeb, Kefah Baqir; Mohammed, Nawal Eltayeb Omer; Bushehab, Abdulaziz Abdullah; Shafey, Marwa Mahmoud (Frontiers in Medicine, 2025)
IntroductionRamadan fasting constitutes a form of intermittent fasting, and it is a religious obligation for healthy adult Muslims; however, there is a lack of comprehensive guidance for individuals diagnosed with sickle cell disease (SCD). This study seeks to identify predictors of fasting capability and investigate the effects of fasting among this patient population.Participants and methodsThis cross-sectional study enrolled adult Muslim patients with SCD from Saudi Arabia. Data were collected through direct interviews using a structured questionnaire with four sections.ResultsA total of 320 patients with SCD were evaluated, with a mean age of 32.6 years (SD ± 11.01) and the majority were females (63.1%). Among these participants, 214 (66.9%) observed Ramadan intermittent fasting (RIF) while 106 (33.1%) did not observe the fasting month or had interrupted fasting. Participants having secondary and university education were nearly twice as likely to fast the entire Ramadan (p = 0.025 and p = 0.003, respectively). History of SCD crises, emergency visits, acute chest syndrome, and intensive care unit admission were all significantly associated with lower odds of fasting the entire month (OR = 0.25, p = 0.019; OR = 0.25, p = 0.001; OR = 0.57, p = 0.035; and OR = 0.46, p = 0.003, respectively). Participants with more than four SCD episodes or more than four emergency room visits had significantly higher odds of experiencing complications within 30 days following Ramadan (OR = 3.31, p < 0.001 and OR = 2.55, p = 0.004, respectively).ConclusionThe effects of observing RIF on individuals with SCD are generally subtle during the month but more significant in the post-fasting phase. The capacity to predict an individual’s ability to fast and likelihood of post-fasting complications is substantially influenced by a range of sociodemographic factors such as education level as well as clinical variables, including frequency of annual hospitalizations, emergency room visits, intensive care unit admissions, occurrences of acute chest syndrome, and the presence of thrombocytosis. A Comprehensive evaluation of these factors will provide enhanced guidance for medical practitioners, facilitating more informed and insightful decisions regarding patient fasting recommendations.